1952
DOI: 10.1007/bf02639813
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid content of meat and poultry before and after cooking

Abstract: SummaryFatty acids distribution of various cuts of pork, lamb, beef, turkey, and chicken before and after cooking were analyzed by the spectrophotometric method. Results indicate that only a small amount of the polyunsaturated fatty acids was lost with ordinary methods of cooking. The reliability of these apparent fatty acid values after cooking is discussed. A table of fatty acid composition of these meats as eaten is also presented for dietary purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1955
1955
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…In the storage fraction (NL), cooking reduced the oleic acid and total MUFA content with a resultant increase in stearic acid and total SFA content. Similarly, Chang and Watts (1952) reported losses of oleic acid that were similar to the overall loss during cooking with moist heat. In the membrane fraction (PL), cooking reduced the percentage of linoleic and linolenic acids, and total PUFA, with a concomitant increase in stearic acid and total SFA content.…”
Section: Discussionmentioning
confidence: 67%
“…In the storage fraction (NL), cooking reduced the oleic acid and total MUFA content with a resultant increase in stearic acid and total SFA content. Similarly, Chang and Watts (1952) reported losses of oleic acid that were similar to the overall loss during cooking with moist heat. In the membrane fraction (PL), cooking reduced the percentage of linoleic and linolenic acids, and total PUFA, with a concomitant increase in stearic acid and total SFA content.…”
Section: Discussionmentioning
confidence: 67%
“…This increase was, however, less noticeable in turkey meat, as compared to samples of chicken meat. The reason for that might be the fact that turkey meat is, in general, leaner than chicken meat, and so over time gives rise to fewer products of lipid oxidation (Chang and Watts 1952). Overall, the number of detected compounds for all the samples increased approximately sevenfold between day 1 and day 5 of storage.…”
Section: Ptr-ms Analysismentioning
confidence: 99%
“…Chang and Watts (1952) reported that mostly saturated fatty acids were detected in fat extracted from chickens, while lesser quantities of linolenic, arachidonic acid and traces of long chain fatty acids were seen. In our study, oleic acid was also dominantly present.…”
mentioning
confidence: 97%